TRENDS IN THE DEVELOPMENT OF THE URBAN REAL ESTATE MARKET IN UKRAINE - Denysenko, N.; Bondarenko, О.; Dovbush, V. (Municipal economy of cities. Series: «Economy science», 2023)
The volatility of external and internal factors affecting the real estate market makes it necessary to study trends and predict the consequences of management decisions to prevent financial losses. The real estate market is a sphere of capital investment in real estate and a system of economic relations arising from real estate transactions. These relations arise when buying and selling real estate, leasing real estate, etc. Depending on the legal framework, external and internal financing conditions, and forms of property ownership, the real estate market is constantly changing and unique to each country, region, and city. To accurately evaluate real estate, it is necessary to monitor in detail all the changes taking place in the market. This article analyzes the factors that influence the formation of supply and demand in the real estate market. Economic factors have the greatest impact, namely: the level and dynamics of population income; differentiation of the population by income level; level of business development and its dynamics; changes in the structure of the business and its profitability; availability of financial resources; the state of alternative and related markets; prices in the real estate market; rental rates; risks of an investment in real estate; construction costs; prices and tariffs for utilities and energy resources. Social factors, such as population dynamics and age structure, the social structure of the population, crime rate and trends in crime, also significantly impact real estate market trends. The interaction of these factors ultimately determines the state and dynamics of supply and demand in the real estate market. At the same time, the direction of their influence may either coincide or differ for supply and demand. This can be better understood by identifying trends in supply and demand and their dependence on these factors. The article examines the history of price dynamics and systematizes the stages of the formation and development of the real estate market in Ukraine. The state of the real estate market during the crisis periods is analyzed and a forecast for the next year is made.